Natural killer cells in sepsis: Friends or foes? - Wang, Fangjie; Cui, Yiqin; He, Dongmei; Gong, Lisha; Liang, Huaping (Frontiers in Immunology, 2023)
Sepsis is one of the major causes of death in severe patients worldwide. Dysregulation of the innate immune responses has been considered to be tightly associated with the pathological process of sepsis. Evidences about the influence of macrophage, neutrophil, and dendritic cell in sepsis have been elucidated, while the roles of NK cell, which is also a fundamental innate lymphocyte specie, seems confusing. In some studies, the activation of NK cell has been reported as a risk factor leading to severe organ damage or death. Controversially, some other studies reveal that triggering NK activity contributes to the alleviation of sepsis. In all, although there are several researches about NK cell in sepsis, it has still not been determined whether they exert exactly detrimental or protective effects. In this review, we will sort out the current animal and clinical studies about NK cell in sepsis from the two opposing aspects, based on which we will further discuss the prospects of NK cell-based immunotherapeutic strategies in treating sepsis.